Water and nitrogen uptake are better associated with resource availability than root biomass. Issue 3 (22nd March 2017) - Kulmatiski, Andrew; Adler, Peter B.; Stark, John M.; Tredennick, Andrew T.
Abstract: Plant uptake of soil water and nitrogen can determine plant growth, community composition, and ecosystem functioning. Despite its importance, resource uptake is typically inferred from root biomass distributions rather than measured directly. Using a depth‐controlled, dual‐tracer experiment, here we show that during peak growing season in a sagebrush‐steppe ecosystem, vertical patterns of root biomass, water uptake, and nitrogen uptake are strikingly different from one another. Half of root biomass (0–188 cm) occurred in the top 24 cm of the soil. Half of water uptake occurred in the top 14 cm. Half of nitrogen uptake occurred in the top 79 cm. Shallow water uptake and deep nitrogen uptake were better correlated with water and nitrogen availability than with root biomass, suggesting that root systems foraged independently for different resources. Root biomass has long been used as a proxy measure of plant access to soil resources, but our results suggest that resource availability may be a better predictor of uptake.